Replace BR1M cash with cards - Hamsawi, Roziana (New Straits Times, 2014)
THE cash handout to low-income Malaysians, or popularly known as Bantuan Rakyat 1Malaysia (BR1M), should not be a long-term or permanent measure, said economists.